2009
DOI: 10.1002/ctpp.200910053
|View full text |Cite
|
Sign up to set email alerts
|

Equation of State of Strongly Coupled Quark–Gluon Plasma – Path Integral Monte Carlo Results

Abstract: A strongly coupled plasma of quark and gluon quasiparticles at temperatures from 1.1Tc to 3Tc is studied by path integral Monte Carlo simulations. This method extends previous classical nonrelativistic simulations based on a color Coulomb interaction to the quantum regime. We present the equation of state and find good agreement with lattice results. Further, pair distribution functions and color correlation functions are computed indicating strong correlations and liquid-like behavior.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 24 publications
0
21
1
Order By: Relevance
“…[70] on the absence of qq bound states above the temperature of the phase transition. This finding is in contrast to our previous results on the SU(2) group [29][30][31][32]. There well-pronounced bound qq states were found just above the critical temperature, which, however, quickly dissolved with the temperature rise.…”
Section: A Equilibrium Propertiescontrasting
confidence: 99%
See 1 more Smart Citation
“…[70] on the absence of qq bound states above the temperature of the phase transition. This finding is in contrast to our previous results on the SU(2) group [29][30][31][32]. There well-pronounced bound qq states were found just above the critical temperature, which, however, quickly dissolved with the temperature rise.…”
Section: A Equilibrium Propertiescontrasting
confidence: 99%
“…[28] for SU (3) group and in Refs. [29][30][31][32] for SU (2) group. In this paper we show that the PIMC method is able to reproduce the QCD lattice equation of state at vanishing baryon-charge density and also yields valuable insight into the internal structure of the QGP.…”
Section: Introductionmentioning
confidence: 99%
“…This view is now supported by first-principle QCD lattice calculations [38,39]. Interestingly, the governing role of correlations may allow for the application of simpler theoretical models and simulations of the QGP, including semiclassical molecular dynamics [40][41][42] and quantum Monte Carlo simulations [43]. The analogy of the collective properties of the QGP and electromagnetic complex plasmas has been pointed out recently [44,45] where it was suggested that results from the latter may give qualitative insights into properties of the former.…”
Section: Significance Of Strong Correlations In Naturementioning
confidence: 91%
“…To this end we use a simple model [9] of the QGP consisting of quarks, antiquarks and gluons interacting via a color Coulomb potential. First results of applications of the PIMC method to study of thermodynamic properties of the nonideal QGP have already been briefly reported in [23,24]. In this paper we present a comprehensive report on the thermodynamic properties.…”
Section: Introductionmentioning
confidence: 95%